Hukum Foto Prewedding dalam Perspektif Fikih Kontemporer - Khan, Zahirah; Zaimatus Sholikhah; Sudirman (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
Prewedding photos have become a popular trend among couples getting married. However, this trend raises various legal questions in Islam because not a few of its practices violate Islamic shari'ah. The purpose of this study is to examine the law of prewedding photos from the perspective of contemporary fiqh. This research uses a qualitative approach with a normative juridical method through analysis of Islamic legal sources such as the Qur'an, and Hadith, as well as fatwas of classical, contemporary scholars, and religious institutions taken from several literatures, such as journals, books, and YouTube. The results show that the scholars' views on prewedding photos vary. Most the scholars forbid prewedding photos because this practice is closer to adultery and contains elements that are contrary to Islamic law, such as ikhtilat, khalwat, tabarruj, and kasyful aurat. On the other hand, some scholars allow prewedding photos under certain conditions, namely as long as they maintain the limits of Islamic law, and have a good purpose. In conclusion, the law of prewedding photos in Islam depends on the context and intention of the perpetrator, as well as the importance of following the guidelines of shari'a to avoid prohibited things.Prewedding photos have become a popular trend among couples getting married. However, this trend raises various legal questions in Islam because not a few of its practices violate Islamic shari'ah. The purpose of this study is to examine the law of prewedding photos from the perspective of contemporary fiqh. This research uses a qualitative approach with a normative juridical method through analysis of Islamic legal sources such as the Qur'an, and Hadith, as well as fatwas of classical, contemporary scholars, and religious institutions taken from several literatures, such as journals, books, and YouTube. The results show that the scholars' views on prewedding photos vary. Most the scholars forbid prewedding photos because this practice is closer to adultery and contains elements that are contrary to Islamic law, such as ikhtilat, khalwat, tabarruj, and kasyful aurat. On the other hand, some scholars allow prewedding photos under certain conditions, namely as long as they maintain the limits of Islamic law, and have a good purpose. In conclusion, the law of prewedding photos in Islam depends on the context and intention of the perpetrator, as well as the importance of following the guidelines of shari'a to avoid prohibited things.